You need to get a better grip on what an equal sign, = , means. It means that you can replace what is on the lhs of the equal sign with what is on the rhs of the equal sign and visa versa. So yes, replace f(1) with 3 and compute f(2).
f(n) is defined in terms of f(n-1), that is to get f(2) you need to know f(1); to get f(3) you need to know f(2); to get f(205) you need to know f(204).
You were given f(1). You now can compute f(2). Knowing f(2) you can then compute f(3). After finding f(3) you can find f(4) .....
if I compute that it would look like this
f(2) = -2f(3) + 1 = -5
f(3) = -2f(3-1) + 1
f(3) = -2f(2) + 1
f( 3) = -2(-5) + 1 = 11
f(4) = -2f(3) +1
f(4) = -2(11) +1
f(4) = -21
f(5) = -2f(4) + 1
f(5) = -2(-21) + 1
f(5) = 43
ok, that makes a lot more sense, I was stuck on simplifying everything and substituting for only f, not f(x) so I was missing what was right in front of me the entire time. Thank you so much for all of your help.